Teška autonomna disfunkcija povezana sa autoimunim tireoiditisom kod post-COVID-19 pacijenta: prikaz slučaja i pregled literature - Milic, Gordana; Milosevic, Milica; Ristic, Masa; Mitovic, Nikola; Dimitrijevic, Ljubica; Salovic, Bojana; Jesic Petrovic, Tanja (Medical Research, 2025)
Introduction We present a case of Hashimoto’s thyroiditis and severe autonomic dysfunction three months after the resolution of the acute phase of COVID-19 infection in a patient with no prior thyroid disease and autonomic dysfunction.Patient Review We discuss clinical presentation, diagnostic evaluation, and subsequent management and follow-up in our patient. Patient tested positive for COVID-19 infection to diagnosis. A 59-year-old female developed Hashimoto’s thyroiditis with normal thyroid function and severe autonomic dysfunction (HRV depressed, HV high ). Conclusion The temporal relationship between COVID-19 infection in patient described here raises the question of the possible effects of COVID-19 on the immune system the thyroid gland and the autonomic nervous system.